2017
DOI: 10.1051/matecconf/201711204013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of aramid fiber laminates with DCPD resin matrix subjected to impact tests

Abstract: Abstract. Research for innovative composite material solutions for impact absorbers is focused on the analysis of their ability to absorb impact energy. For this purpose, aramid fiber laminate with DCPD resin matrix was prepared. Laminate samples were tested on the drop test and were subjected to ballistic loads. The laminate structure was modeled with ABAQUS software with the objective to optimize and estimate the ability to absorb impact energy in the range of high speeds (350m/s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Figure 14.Comparison of obtained deflection value with other studies; previous studies taken from[54], E-glass, SB 21, E-glass, Kevlar 129, E-glass + Epoxy for 50 and 70 layers taken from[57], 19 and 17 layers of Kevlar + Epoxy taken from[58].…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…Figure 14.Comparison of obtained deflection value with other studies; previous studies taken from[54], E-glass, SB 21, E-glass, Kevlar 129, E-glass + Epoxy for 50 and 70 layers taken from[57], 19 and 17 layers of Kevlar + Epoxy taken from[58].…”
mentioning
confidence: 72%
“…So far, no widely used DCPD matrix in ballistic applications has been found in the literature, apart from previous research by the co-authors of this article in the following papers [50,54]. Further development of the methods used to prepare ballistic shields is an element of novelty, thanks to which it is possible to constantly strive to reduce BFS parameters.…”
Section: Comparison Of the Obtained Deflection Values To Other Matric...mentioning
confidence: 96%
See 2 more Smart Citations
“…The results showed that the samples containing the ceramic layer absorb 50% of the bullet energy and that the steel balls absorb 35% of the bullet energy. M. Bocian et al [16] studied and analyzed a shield plate made of Aramid fiber with a polymer. The plate was digitally recorded using the ABAQUS program to resist a bullet 9 × 19 mm and speed 350 m/s, the results showed the ability of the plates to absorb all energy from bullets and compare with the practical results.…”
Section: Introductionmentioning
confidence: 99%